2013
DOI: 10.1103/revmodphys.85.1473
|View full text |Cite
|
Sign up to set email alerts
|

Colloquium: Artificial spin ice: Designing and imaging magnetic frustration

Abstract: Frustration -the presence of competing interactions -is ubiquitous in the physical sciences and is a source of degeneracy and disorder, which in turn give rise to new and interesting physical phenomena. Perhaps nowhere does it occur more simply than in correlated spin systems, where it has been studied in the most detail. In disordered magnetic materials, frustration leads to spin-glass phenomena, with analogies to the behavior of structural glasses and neural networks. In structurally ordered magnetic materia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
543
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 494 publications
(549 citation statements)
references
References 114 publications
5
543
0
1
Order By: Relevance
“…Arrays of interacting, single-domain nanomagnets known as artificial spin ice have proved to be useful model systems with which to experimentally explore the microscopic nature of geometrical frustration [6][7][8] . Simple square and kagome artificial spin ice lattices have been subject to intense study because they provide unique insight into the consequences of frustrated magnetism, such as residual entropy 9,10 and magnetic charge excitations [11][12][13][14] .…”
mentioning
confidence: 99%
“…Arrays of interacting, single-domain nanomagnets known as artificial spin ice have proved to be useful model systems with which to experimentally explore the microscopic nature of geometrical frustration [6][7][8] . Simple square and kagome artificial spin ice lattices have been subject to intense study because they provide unique insight into the consequences of frustrated magnetism, such as residual entropy 9,10 and magnetic charge excitations [11][12][13][14] .…”
mentioning
confidence: 99%
“…The system reveals a rich phase behavior when skyrmion-current interactions compete with structural confinement strength. In contrast to lattices of interacting nanoscale particles/islands such as artificial spin ice [43,44], or colloids [71,72,105], the spin-torque reconfigurability of the proposed skyrmion ices makes them compatible with standard spintronic devices such as magnetic tunnel junctions and thus straightforwardly integrable to the existing semiconductor manufacturing processes.…”
Section: Discussionmentioning
confidence: 99%
“…The observed disordered states, composed of a mixture of ice-rule-obeying and ice-rule-breaking vertices [43], may arise due to the relatively weak magnetic interactions between the nanomagnets and the relatively high energy barrier between the two possible nanomagnet states, as well as from quenched disorder effects in the nanomagnet array [44]. Recently, it was demonstrated that the GS could be approached more closely by using certain dynamical annealing protocols [43,51,70].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations